Social Media Perspectives ın Informational Society - Kakhidze, Irakli (European Scientific Journal, ESJ, 2017)
The main aspects of social media and various attempts of its interpretation are reviewed in the article. The concept, main functions of social media are highlighted, its positive and negative sides and expected tendencies of development are presented. Position of social media optimists is shared in the article according to which, functions and importance of social media is positively seen and understood despite certain resistance. The above phenomenon entirely changed the communicative paradigm of the epoch which became a reason for significant social transformation, on its part. In particular, engagement of citizens in social-political processes, social awareness and level of democracy sharply increased which predetermined significant expansion of area of opportunities of an individual.